2022
DOI: 10.3390/ijerph19095721
|View full text |Cite
|
Sign up to set email alerts
|

Perception of National Park Soundscape and Its Effects on Visual Aesthetics

Abstract: Soundscape perception is a very weak link in the national park landscape evaluation system in China. A thorough understanding of soundscapes and their effects on visual aesthetics is important for the management of national park landscapes. In this study, features of soundscapes (e.g., loudness, frequency, preference, and auditory satisfaction) were investigated based on 394 valid questionnaires of residents in the Qianjiangyuan National Park Pilot Area. The effects of soundscape on visual aesthetics were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Aletta examined the conceptual framework of the soundscape model [14]. Wang studied the perception of soundscapes in national parks and their impact on visual aesthetics [15]. Sun, Minkai and Marafa [16,17] did pioneering work in the field of soundscape research in classical Chinese gardens, exploring the creation of soundscapes within classical Chinese gardens from the perspective of sound sources.…”
Section: Urban Forest Park Acoustic Environment Studymentioning
confidence: 99%
“…Aletta examined the conceptual framework of the soundscape model [14]. Wang studied the perception of soundscapes in national parks and their impact on visual aesthetics [15]. Sun, Minkai and Marafa [16,17] did pioneering work in the field of soundscape research in classical Chinese gardens, exploring the creation of soundscapes within classical Chinese gardens from the perspective of sound sources.…”
Section: Urban Forest Park Acoustic Environment Studymentioning
confidence: 99%
“…The research objects of soundscape perception characteristics are mainly different spatial environments, such as parks, green spaces, neighborhoods, classrooms, etc. [11][12][13][14][15]. For example, Zhang X et al…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this link has not been fully verified [19]. Wang et al studied the impact of soundscape perception behavior on vision and confirmed that sound frequency, sound preference, and auditory satisfaction had an impact on visual perception [20]. Li et al used heart rate (HR), heart rate variability (HRV), and other indices to explore the tendency of the physiological indices and subjective recoverability in environmental audio-visual interaction [21].…”
Section: Introductionmentioning
confidence: 99%